Fish Scale-Derived Scaffolds for Culturing Human Corneal Endothelial Cells - Mohit Parekh; Bert Van den Bogerd; Nadia Zakaria; Diego Ponzin; Stefano Ferrari (Stem Cells International)
Purpose. To investigate the biocompatibility of fish scale-derived scaffolds (FSS) with primary human corneal endothelial cells (HCEnCs). Methods. HCEnCs were isolated from 30 donor corneas in a donor-matched study and plated in precoated Lab-Tek slides (n=15) and FSS (n=15). Cell morphology, proliferation/migration, and glucose uptake were studied (n=30). Hoechst, ethidium homodimer, and calcein AM (HEC) staining was performed to determine viability and toxicity (n=6). The cell surface area was calculated based on calcein AM staining. HCEnCs were stained for ZO-1 (n=6) to detect tight junctions and to measure cell morphology; Ki-67 (n=6) to measure proliferating cells; and vinculin to quantify focal adhesions (n=6). The formation of de novo extracellular matrix was analyzed using histology (n=6). Results. HCEnCs attach and grow faster on Lab-Tek slides compared to the undulating topography of the FSS. At day 11, HCEnCs on Lab-Tek slide grew 100% confluent, while FSS was only 65% confluent (p=0.0883), with no significant difference in glucose uptake between the two (p=0.5181) (2.2 μg/mL in Lab-Tek versus 2.05 μg/mL in FSS). HEC staining showed no toxicity. The surface area of the cells in Lab-Tek was 409.1 μm2 compared to 452.2 μm2 on FSS, which was not significant (p=0.5325). ZO-1 showed the presence of tight junctions in both conditions; however, hexagonality was higher (74% in Lab-Tek versus 45% in FSS; p=0.0006) with significantly less polymorphic cells on Lab-Tek slides (8% in Lab-Tek versus 16% in FSS; p=0.0041). Proliferative cells were detected in both conditions (4.6% in Lab-Tek versus 4.2% in FSS; p=0.5922). Vinculin expression was marginally higher in HCEnCs cultured on Lab-Tek (234 versus 199 focal adhesions; p=0.0507). Histological analysis did not show the formation of a basement membrane. Conclusions. HCEnCs cultured on precoated FSS form a monolayer, displaying correct morphology, cytocompatibility, and absence of toxicity. FSS needs further modification in terms of structure and surface chemistry before considering it as a potential carrier for cultured HCEnCs.